From Da'wa To Capital: Religious Commodification and Identity Consolidation in Integrated Islamic Schools - Senata Adi Prasetia (DINIKA : Academic Journal of Islamic Studies, 2026)
This study examines the shifting orientation of Integrated Islamic Schools (Sekolah Islam Terpadu, SIT) from a mission of da’wa (Islamic propagation) toward a strategy of capital accumulation. The expansion of SIT reflects the emergence of a new Muslim middle class that seeks to express religious identity while simultaneously displaying status, class position, and social taste as modern Muslims. This study is based on field research that focuses on religious commodification, stakeholder motivations, consumer rationales for identity consolidation, and the dynamic interactions of Indonesian middle-class Muslims, as well as their implications for social cohesion. Employing on Pierre Bourdieu’s framework of economic, social, and cultural capital, this study demonstrates how SITs, initially established as Islamic educational institutions, have gradually adopted economic strategies to ensure institutional sustainability. Furthermore, this study shows how SITs position themselves as exclusive, modern, and market-oriented Islamic schools, primarily targeting urban middle-class Muslim consumers. This form of commodification reflects a growing demand for religiously infused education as both a means of social mobility and a strategy for preserving religious identity. More broadly, this phenomenon can be linked to Islamic revivalism as a response to modernity and secularization, illustrating how SITs function simultaneously as vehicles for religious reaffirmation and economic expansion.